Tác động bất đối xứng của biến động giá dầu đến thị trường chứng khoán Việt Nam: Tiếp cận mô hình phi tuyến tính ARDL - Phạm Thị Tuyết Trinh; Võ Lê Linh Đan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This study investigates the asymmetric impact of the oil price fluctuation on the Vietnamese stock market in the short run and long run after the financial crisis in 2008. By employing non-linear autoregressive distributed lag model (ARDL) associated with the bound test to monthly data of VN-Index, crude oil Brent price, industrial production index, and money supply, the study comes to following noticeable results. First, in the long run, the oil price has the significant negative impact on the domestic stock market, implying an increase in oil price leads to downward movement of the stock market and a decrease in oil price causes the stock market to move upward. Second, the long run impact of the oil price increase on the stock market is more prominent than oil price decrease, reflecting the asymmetric impact of oil price fluctuation on the Vietnam stock market. Third, in the short run, the stock market has an opposite response with the oil price fluctuation compared with in the long run.
Keywords: ARDL; Non-linear; Price oil; Stock market